Effect of the Extract of Mix Flowers (Chamomilla, Lavender and Rose) on Growth and Yield of Broad Bean (Vicia faba L.) - R. W. Mahmood (Journal of Madenat Alelem University College, 2015)
Biological experiment was conducted in the botanical garden of College of Education for Pure Science (Ibn Al-Haitham) during the growing season 2012-2013 to study the effect of extracts of mix flowers chamomilla (Matricaria chamomilla L.), lavender (Lavandula officinalis L.) and rose (Rosa gallica L.) with two concentrations 25% and 35% on vegetative characteristics and yield components of broad bean (Viciafabia L.). The results showed that the mixture of flowers extract affects significantly on the height of plant, number of leaves, surface area of leaf, leaf area relative, dry weight and level of protein in seeds.